Ministry of Social Solidarity Decree No. 392 Of The Year 2016 Regarding the Rules Governing the Disbursement of the Increase in Pensions Prescribed by Law No. 60 of the year 2016 = وزارة التضامن الإجتماعى قرار رقم 392 لسنة 2016 بقواعد صرف زيادة المعاشات المقررة بالقانون رقم 60 لسنة 2016 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic